MANAJEMEN KINERJA KEPALA SEKOLAH UNTUK MEMENUHI STANDAR PENGELOLAAN SMP NEGERI 6 JELIMPO - Abdon Abdon; Sukmawati Sukmawati; M. Syukri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study aims at the management of the principal's performance to meet the management standards of SMPN 6 Jelimpo. The research method used descriptive research with a qualitative approach. The results of the study : 1) The principal's performance planning in meeting the management standards has been fulfilled , 2) Organizing the head of SMPN 6 Jelimpo has compiled an organizational structure in relation to the division of main duties and functions of teachers and socialized 3)Implementation of the performance of the head of SMPN 6 Jelimpo refers to supervision guidelines in the form of managerial supervision instruments ,4) Forms of performance of the head of SMPN 6 Jelimpo namely by conducting managerial supervision by supervisors and academic supervision by the head 5) Evaluation of the performance of the principal of SMPN 6 Jelimpo is carried out in the form of an assessment of the performance of the principal carried out by the supervisor, the assessment of the performance of the teacher carried out by the principal and the achievement of the performance results of the principal and teacher (PNS) in the form of employee performance targets at the end of each year. Keywords:management, management standards, principal performance